Evil, holocaust and theodicy in Gabriel Marcel (Tempo e Argumento, 2023)
The review focuses on the release, in the Italian version, of Mal, holocausto, teodicéia, curated by Franco Riva and Paolo Scolari, from the publisher Castelvecchi, in Rome, in 2022.